2002
DOI: 10.1055/s-2002-23198
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Insulin-Like Growth Factor Binding Protein-1 is Associated with Increased Cardiovascular Mortality in Elderly Men

Abstract: Insulin-like growth factor binding protein-1 (IGFBP-1) has been implicated in the development of cardiovascular disease, but it is not known whether IGFBP-1 is related to cardiovascular mortality. We examined the relation of circulating IGFBP-1 to death from coronary heart disease, cardiovascular disease, and all causes in a cohort study consisting of 622 men aged 65 - 84 years, at baseline in 1984. Fasting serum IGFBP-1 and other risk factors were measured in 1984 and 1989. Cardiovascular events for those who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 24 publications
1
40
1
Order By: Relevance
“…However, Kaplan et al (17) reported an association of higher IGFBP1 with mortality, which did not reach statistical significance. Hu et al (18) reported that higher IGFBP1 was associated with all-cause mortality, and Harrela et al (32) reported higher IGFBP1 predicted all-cause and coronary heart disease mortality. Despite lower IGFBP1 levels being associated with less favourable indices of cardiovascular risk and increased odds of metabolic syndrome, we found no evidence that reduced IGFBP1 levels predicted CVD mortality; in fact, the contrary trend was present.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kaplan et al (17) reported an association of higher IGFBP1 with mortality, which did not reach statistical significance. Hu et al (18) reported that higher IGFBP1 was associated with all-cause mortality, and Harrela et al (32) reported higher IGFBP1 predicted all-cause and coronary heart disease mortality. Despite lower IGFBP1 levels being associated with less favourable indices of cardiovascular risk and increased odds of metabolic syndrome, we found no evidence that reduced IGFBP1 levels predicted CVD mortality; in fact, the contrary trend was present.…”
Section: Discussionmentioning
confidence: 99%
“…Among diabetics with acute myocardial infarction (median age 70 years) in the Diabetes Mellitus Insulin-Glucose Infusion in Acute Myocardial Infarction 2 (DIGAMI 2) trial, high IGFBP-1 predicted cardiovascular events and death (22). The Seven Countries Study identified high IGFBP-1 level as a predictor of cardiovascular mortality among 65 -84 year old men (23). Prior data from older populations suggest an association between high IGFBP-1 and favorable levels of some metabolic factors such as obesity and lipids (32), as was also shown in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Aging, cachectic conditions, malnutrition, inflammatory cytokines, and oxidative stress all increase IGFBP-1 expression (15)(16)(17)(18)(19)(20)(21), which may in turn lead to inhibition of anabolic IGF-I effects by IGFBP-1 during catabolic states. High circulating IGFBP-1 levels predict cardiovascular events after myocardial infarction (22) and cardiovascular mortality among apparently healthy older men (23). Prior data also indicate increased IGFBP-1 levels in CHF patients (24) which suggests that high circulating IGFBP-1 levels may be a CHF risk factor, although no prior studies of IGFBP-1 and incident CHF are available.…”
mentioning
confidence: 99%
“…Furthermore, clinical studies have shown that low levels of IGF-I and IGF binding proteins 1 and 3 (IGFBP-1 and IGFBP-3) are related to AMI or angiographically assessed coronary heart disease [7][8][9][10]. However, the findings are not consistent as previous studies also have shown that patients with coronary heart disease have increased levels of both IGF-I [11] and IGFBP-1 [12] and patients with low circulating IGF-I levels in combination with high IGFBP-3 levels had a significantly increased risk of developing ischaemic heart disease during a 15-year follow-up period [13].…”
Section: Introductionmentioning
confidence: 85%